Systemic Cryotherapy and Its Effects on the Cardiovascular and Autonomic Nervous Systems in the Context of Post-Exercise Recovery - A Narrative Review of the Literature - Sobczak, Wiktoria Laura; Kulik, Szymon; Placek, Anna; Pyzik, Alicja; Polakowska, Anna; Borkowska, Karolina (Quality in Sport, 2026)
Systemic cryotherapy involves brief exposure of the whole body to extremely low temperatures, usually in a cryochamber or cryosauna. It is increasingly used in medicine and sport, particularly due to its potential effects on the cardiovascular system, autonomic regulation and post-exercise recovery. This review aimed to summarise current knowledge regarding physiological responses to whole-body cryotherapy, with emphasis on circulatory and autonomic nervous system changes and their relevance to recovery. This narrative review analysed experimental, interventional and observational studies identified in the PubMed, Scopus and Web of Science databases. Exposure to extreme cold induces rapid thermoregulatory, haemodynamic and neurohormonal responses, including peripheral vasoconstriction, central blood volume redistribution, transient blood pressure and heart rate changes, and modulation of autonomic nervous system activity. Some studies observed increased parasympathetic activity after treatment; however, their magnitude and duration depended on the protocol, study population and timing of assessment. Available evidence suggests that systemic cryotherapy may reduce subjective fatigue and muscle soreness after exercise, whereas its effects on objective recovery markers, muscle damage and performance remain inconclusive. Interpretation is limited by small sample sizes, heterogeneous exposure protocols and insufficient methodological standardisation. Systemic cryotherapy may complement recovery strategies; however, further research is needed to confirm its efficacy and safety.